The Contribution of Listening Skills and Learning Motivation to Arabic Learning Outcomes at Muhammadiyah Vocational School, Batam City - Yelni Yasri; Ambiyar Ambiyar; Sukardi Sukardi (Jurnal Vokasi Mekanika (VoMek), 2025)
Arabic language learning at Muhammadiyah Vocational School in Batam City faces several challenges: the perception of Arabic as a difficult subject, students’ anxiety in learning Arabic, ineffective classroom management, unstructured listening practice, and varying levels of learning motivation. Therefore, this study aims to analyze the contribution of listening skills and learning motivation, both partially and simultaneously, to the Arabic learning outcomes of students at Muhammadiyah Vocational School in Batam City. Using a quantitative descriptive-correlational design with a sample of 132 tenth-grade students, learning outcomes data were obtained through tests, while listening skills and learning motivation were measured using questionnaires; analysis was conducted through correlation and multiple regression (SPSS). The results show that listening skills contributed positively to learning outcomes with a determination coefficient of 11.9% (effective contribution = 9.12%; relative contribution = 37.23%), learning motivation contributed 41.9% (effective contribution = 38.71%; relative contribution = 62.74%), and simultaneously both contributed 44.8% to Arabic learning outcomes. Practically, strengthening structured listening practices (authentic oral input, periodic assessments) and motivational interventions (goal setting, formative feedback, varied methods) are recommended to improve performance; socially, enhancing listening literacy and motivation is expected to foster a more focused, diligent, and collaborative academic culture within the vocational school environment. This study provides added value by integrating the analysis of the foundational role of listening skills and the psychological factor of motivation in Arabic learning within the vocational context, and by presenting estimates of both partial and simultaneous contributions as a basis for designing policies and teaching strategies